POLITIK ON THE NET: IMPLIKASI MEDIA SOSIAL TERHADAP ELEKTABILITAS CAPRES PADA PEMILU 2019 DIKALANGAN PEMILIH MILLENIAL KOTA KENDARI - Sri Hadijah Arnus (Al-MUNZIR, 2020)
ABTRACTThe purpose of this study was to determine the implications of political messages on social media on the electability of presidential candidates in the 2019 elections among millennial voters in Kendari City. This type of research is descriptive qualitative. The method used in this research is interviews and documentation. The results of this study explain that Based on the observations of researchers on social media Facebook, political messages related to the 2019 presidential election are classified into three parts, namely first, those related to the vision, mission and work programs of the presidential candidate pairs, secondly those related to religious, racial and class sentiments and the third is messages related to the personal life of the presidential candidate pair, whether it is related to family, friends, and so on. The presidential candidate pair number 2 and their supporters are the pairs who are most aggressive in making posts on social media so that the presidential candidate pair number 2 tends to be more popular on social media compared to the presidential candidate pair number 1. Political messages on social media as a medium to introduce and increase the popularity of candidates but has no implications for the electability of millennial voters in Kendari City.Keywords: Political Communication, Social Media, Millennial Voters, Presidential Candidates, 2019 Election